2019
DOI: 10.1051/0004-6361/201935129
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of slowly rotating asteroids: results from a targeted survey

Abstract: Context. Earlier work suggests that slowly rotating asteroids should have higher thermal inertias than faster rotators because the heat wave penetrates deeper into the sub-surface. However, thermal inertias have been determined mainly for fast rotators due to selection effects in the available photometry used to obtain shape models required for thermophysical modelling (TPM). Aims. Our aims are to mitigate these selection effects by producing shape models of slow rotators, to scale them and compute their therm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…We found our derived diameters and albedos to be broadly consistent with the NEATM-derived values with the WISE thermal data set (Mainzer et al 2019). Our derived thermal inertia were broadly consistent with the trends found with diameter (e.g., Delbo' et al 2007) and rotation period (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) in the literature, though in both cases the large uncertainties on thermal inertia limit the conclusions we were able to draw from the data. We applied a linear fit to the diameters and thermal inertia normalized to 1 au of the form log[Γ] = α + β log[D], we find best-fit values of α = 2.667 ± 0.059 and β = −0.467 ± 0.044 for our sample alone and α = 2.509 ± 0.017 and β = −0.352 ± 0.012 when combined with literature estimates.…”
Section: Conclusion and Future Prospectssupporting
confidence: 88%
See 1 more Smart Citation
“…We found our derived diameters and albedos to be broadly consistent with the NEATM-derived values with the WISE thermal data set (Mainzer et al 2019). Our derived thermal inertia were broadly consistent with the trends found with diameter (e.g., Delbo' et al 2007) and rotation period (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) in the literature, though in both cases the large uncertainties on thermal inertia limit the conclusions we were able to draw from the data. We applied a linear fit to the diameters and thermal inertia normalized to 1 au of the form log[Γ] = α + β log[D], we find best-fit values of α = 2.667 ± 0.059 and β = −0.467 ± 0.044 for our sample alone and α = 2.509 ± 0.017 and β = −0.352 ± 0.012 when combined with literature estimates.…”
Section: Conclusion and Future Prospectssupporting
confidence: 88%
“…Some earlier studies (e.g., Harris & Drube 2016) have suggested that slow rotators should present higher thermal inertia due to thermal observations being able to probe more deeply into an asteroid's surface. Other more recent studies (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) have found no excess of high thermal inertia values among slow rotators (conventionally defined as asteroids with P > 12 hours), nor for low thermal inertia values among fast rotators. In our sample, we likewise find thermal inertia values greater than 100 J m −2 s −0.5 K −1 to be generally present across our entire rotation period range, though we note that our sample is sparsely populated with rotation periods longer than 30 hours (Fig.…”
Section: Relationship With Rotation Periodmentioning
confidence: 84%
“…It was thus hypothesized that slow rotators (i.e., rotation periods longer than 12 hours) should on average present higher thermal inertia than those of fast rotators. While early studies such as Harris & Drube (2016) and Marciniak et al (2018) appeared to confirm this trend, later studies with larger samples of slow rotators (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) found no such relation.…”
Section: Introductionmentioning
confidence: 95%
“…A handful of asteroids with thermal inertias presented here have previous estimates from the works of Hanus et al (2018), Marciniak et al (2019), andPravec et al (2019). We depict all these estimates in Fig.…”
Section: Results and Analysismentioning
confidence: 96%
“…The thermal wave can be expressed in terms of the thermal skin depth, l s , which is the length scale over which the diurnal temperature variation changes by a factor of e ≈ 2.71828: l s = kP rot /2πρc s . On the other hand, Marciniak et al (2019) used a TPM to derive thermal inertias of slow-rotators and found no correlation between the two variables.…”
Section: Introductionmentioning
confidence: 98%